Peter Doherty on challenges and opportunities of pig production in Southeast Asia - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, speaks about challenges and opportunities of pig production in Southeast Asia. Filmed in September 2016